Visualisasi Bandwidth Usage Untuk Universitas Kristen Petra Menggunakan Tools TSTAT - Limanto, Yohan Alvin; Andjarwirawan, Justinus; Palit, Henry Novianus (Jurnal Infra, 2016)
Internet is one of the fastest growing Information Technology. There is a lot of information which can easily be obtained through the Internet. Computer network system is needed for a person to use or access it. Along with the increasing number of Internet users, Petra Christian University has been doing various ways in using the internet well, such as increasing bandwidth and also replacing the Internet cable lines with fiber cable. However, there are still some problems like delayed access, etc.Therefore, this manuscript describes the development of bandwidth usage visualization to help Petra Christian University, particularly its network division, to obtain information about Internet bandwidth usage. The application which is used for generating the bandwidth usage visualization is TSTAT. TSAT is a tool for analyzing the traffic passing through the network layer and it can only be used in a UNIX-based operating system such as LINUX, OS X, and other variants.Â Collected traffic data will be analyzed using TSTAT and the results (in RRD format) are stored in mysql database. Storing to database is necessary since the RRD storage capacity is so limited (fixed) that, when the capacity is full, the earliest data will be overwritten. Afterward, data from database will be visualized by using RDDtools, and the display result in the form of graph will be presented on the website by using PHP language. Based on 15-minute traffic data capture, 95,8% of the traffic is TCP protocol, while 4,2% is UDP.